Specialist palliative care, psychology, interstitial lung disease (ILD) multidisciplinary team meeting: a novel model to address palliative care needs. Issue 1 (19th December 2018) - Barratt, Shaney L; Morales, Michelle; Speirs, Toby; Al Jboor, Khaled; Lamb, Heather; Mulholland, Sarah; Edwards, Adrienne; Gunary, Rachel; Meek, Patricia; Jordan, Nikki; Sharp, Charles; Kendall, Clare; et al.
Abstract : Introduction: Patients with progressive idiopathic fibrotic interstitial lung disease (ILD), such as those with idiopathic pulmonary fibrosis (IPF), can have an aggressive disease course, with a median survival of only 3–5 years from diagnosis. The palliative care needs of these patients are often unmet. There are calls for new models of care, whereby the patient's usual respiratory clinician remains central to the integration of palliative care principles and practices into their patient's management, but the optimal model of service delivery has yet to be determined. Methods: We developed a novel, collaborative, multidisciplinary team (MDT) meeting between our palliative care, psychology and ILD teams with the principal aim of integrating specialist care to ensure the needs of persons with ILD, and their caregivers were identified and met by referral to the appropriate service. The objective of this study was to assess the effectiveness of this novel MDT meeting on the assessment of a patient's palliative care needs. Results: Significant increases in advance care planning discussions were observed, in conjunction with increased referrals to community courses and teams, following introduction of this novel MDT. Conclusions: Our results suggest that our collaborative MDT is an effective platform to address patients' unmet palliative care needs. Further work is required to explore the effect of our model on achieving the preferred place of death and reductions in unplanned hospital admissions.